2006
DOI: 10.1002/cne.21011
|View full text |Cite
|
Sign up to set email alerts
|

Histological and cytological study of the bed nuclei of the stria terminalis in adult rat. II. Oval nucleus: Extrinsic inputs, cell types, neuropil, and neuronal modules

Abstract: The oval nucleus (Ov) of the bed nuclei of the stria terminalis was studied in adult rats. The Ov is composed of 11 neuron types distributed into a shell and a core domain. The stria terminalis, internal capsule, ventral amygdaloid pathway, and medial forebrain bundle are the main sources of afferents to the neuropil of the Ov. The nucleus shell contains abundant intrinsic neurons possibly connected among themselves and with the core by centripetal axon collaterals. Series of intrinsic neurons in the shell, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
72
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 63 publications
8
72
0
Order By: Relevance
“…Three prior Golgi studies described the morphological properties of BNST-A neurons (McDonald 1983;Larriva-Sahd 2004, 2006. For the juxtacapsular nucleus, there is consensus that the majority of neurons are small cells with spiny and often bipolar dendritic trees (McDonald 1983;Larriva-Sahd 2004), consistent with our results.…”
Section: Morphological Correlates Of Electroresponsive Propertiessupporting
confidence: 90%
See 1 more Smart Citation
“…Three prior Golgi studies described the morphological properties of BNST-A neurons (McDonald 1983;Larriva-Sahd 2004, 2006. For the juxtacapsular nucleus, there is consensus that the majority of neurons are small cells with spiny and often bipolar dendritic trees (McDonald 1983;Larriva-Sahd 2004), consistent with our results.…”
Section: Morphological Correlates Of Electroresponsive Propertiessupporting
confidence: 90%
“…For the juxtacapsular nucleus, there is consensus that the majority of neurons are small cells with spiny and often bipolar dendritic trees (McDonald 1983;Larriva-Sahd 2004), consistent with our results. For BNST-AL, there is also agreement that the dominant cell type is characterized by an ovoid soma from which emerge four to five dendrites that branch several times, are aspiny proximally, moderately to densely spiny more distally, and often exhibit dendritic varicosities (McDonald 1983;Larriva-Sahd 2006). McDonald (1983) McDonald (1983) reported for BNST-AM neurons, a majority of these cells contribute few dendritic branches that ramify sparingly and exhibit a low spine density.…”
Section: Morphological Correlates Of Electroresponsive Propertiesmentioning
confidence: 75%
“…Although not reporting in this study, we also found similar results with non-CRHÏ© BNST neurons. The extent of strong inhibitory connections is consistent with earlier findings showing that GABAergic neurons make up a predominant portion of the general makeup of adBNST and glutamatergic neurons only account for a minority of the overall population (Daniel and Rainnie 2016;Larriva-Sahd 2006;Nguyen et al 2015). Given that BSNT receives strong extrinsic excitatory inputs from the amygdala and other brain regions (Daniel and Rainnie 2016;Kim et al 2013), strong local inhibitory connections can play an important role in modulation of these extrinsic inputs.…”
Section: Lsps Mapping Of Excitatory and Inhibitory Synaptic Circuits supporting
confidence: 90%
“…1, A and B), thus enabling consistent sampling of the targeted cell types. CRHÏ© neurons in the BNST have been studied and were reported to have heterogeneous morphological and electrophysiological phenotypes (Larriva-Sahd 2004, 2006). Our post hoc intracellular biocytin staining of the recorded CRHÏ© BNST neurons showed diverse cell morphology (Fig.…”
mentioning
confidence: 99%
“…The BST can be roughly divided into anterior and posterior subdivisions, each containing several nuclei, which can be identified based on their projection pattern and neurochemical identity (Cassell et al, 1986;Day et al, 1999;Larriva-Sahd, 2004, 2006McDonald,1983;Moga et al,1989;Veinante and Freund-Mercier, 1997 posterior group (BSTpost) may contribute more to reproduction and defense. However, the anterior and posterior BST are highly interconnected, ruling out unrelated or distinct functions for the two general areas.…”
mentioning
confidence: 99%